Serological researches for parainfluenza type 3 virus infection in the cattle of konya agriculture management - Feridun ÖZTÜRK (Eurasian Journal of Veterinary Sciences)
A disease progressed with respiratoric symptoms in the cattle of Konya Agriculture Management was serologically determined as PIV- 3 disease. With this aim, the 79 cattle blood sera were collected and examined for antibodies to PIV- 3 by microneut:ralisation test. At the end of the microneutralisation test, at a dilution of 1:5, the 40 (50."63%) cattle blood sera were found. for the neutralizing antibodiE~s to PIV- 3.